Pengaruh Profitabilitas Terhadap Nilai Perusahaan dengan Manajemen Laba sebagai Variabel Moderating - Moses Oliver Dore Huriquduq (Yayasan Literasi Ilmiah Indonesia, 2022)
This study aims to test whether profitability affects firm value with earnings management as a moderating variable. This study took a sample of manufacturing companies listed on the Indonesia Stock Exchange. The type of data used in this research is secondary data in the form of company financial reports. During the 2019-2021 period, there were 15 manufacturing companies. The sampling method used in this study was purposive, namely the sampling method determined by the researcher based on certain criteria. Manufacturing companies taken based on the research criteria are 15 sample companies. The results of the study include (1) Profitability has a positive and significant effect on earnings management, (2) Earnings management has a positive and significant effect on firm value, (3) profitability has a positive and significant effect on firm value, and (4) profitability has a positive effect on firm value moderated by earnings management.